2020
DOI: 10.1029/2019wr026234
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Model of Arsenic Mobility in the Shallow Alluvial Aquifers Near Venice (Italy) Elucidated Through Machine Learning and Geochemical Modeling

Abstract: This work proposed a novel method to elucidate the controls of As mobility in complex aquifers based on an unsupervised machine learning algorithm, Self-Organizing Map (SOM), and process-based geochemical modeling. The approach is tested in the shallow aquifers of the Venetian Alluvial Plain (VAP) near Venice, Italy, where As concentrations seasonally and locally exceed recommended drinking water limits. SOM was fed using information from two geochemical surveys on eight VAP boreholes, and continuous reading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 77 publications
3
4
0
Order By: Relevance
“…Our stochastic analysis revealed that the shallow aquifers in the WAA are more sensitive to rainfall-controlled reactions than deeper parts of the aquifers. On the one hand, this corroborates and extends the validity of the conclusions by Dalla Libera et al [29]. On the other hand, the results are well aligned with the conclusions from other studies that already identified a link between As mobility and aquifer recharge.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our stochastic analysis revealed that the shallow aquifers in the WAA are more sensitive to rainfall-controlled reactions than deeper parts of the aquifers. On the one hand, this corroborates and extends the validity of the conclusions by Dalla Libera et al [29]. On the other hand, the results are well aligned with the conclusions from other studies that already identified a link between As mobility and aquifer recharge.…”
Section: Discussionsupporting
confidence: 91%
“…This site is a well-characterized subset of the Venetian Alluvial Plain in Northern Italy (Figure 1). Previous works on the area [26][27][28][29] have generally concluded that As concentrations can be considered a random spatiotemporal variable, amenable to be modelled using probabilistic and geostatistical analysis. This makes the WAA an appealing case study to evaluate the actual usefulness of the stochastic model to predict the PNE of arsenic concentrations above the 10 μgL −1 and 50 μgL −1 critical thresholds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed information on SOM can be found in Kohonen (1982Kohonen ( , 1990Kohonen ( , 2001Kohonen ( , 2013 and Kalteh et al (2008). The SOM method has recently been used in the analysis of groundwater geochemical data in a coastal aquifer near Venice (Dalla Libera et al 2020) and in geochemical pattern recognitions of deep thermal groundwater in South Korea (Kim et al 2020).…”
Section: Self-organising Map Analysismentioning
confidence: 99%